MARKETING CAMPAIGN FINANCIAL REPORTING: LINKING COMMUNICATIONS WITH ACCOUNTABILITY - Loso Judijanto; Desi Yuniarti (CV. Adiba Aisha Amira, 2024)
Marketing campaign financial reporting is essential in the modern business world. This report links marketing communication activities with the financial responsibility of the company. The study in this research uses the literature research method. The results show that a complete and easy-to-understand financial report is essential. Such reports can help show the value of marketing activities, better organise the use of money, and make marketing teams more accountable for their work. The research also found that it is important to combine financial figures with other non-monetary matters in the report. In addition, it is also helpful to use attractive images or graphics and make the report suitable for the different people who read it.